Mesures de compensation écologique : risques ou opportunités pour le foncier agricole en France ? - Claire Etrillard (Éditions en environnement VertigO, 2015)
Compensation measures require a developer to offset the negative effects of the project. Two types of approaches are possible. The first one is based on the compensation claim : in this case the developer looks for surfaces on which he can offset its grip. The second focuses on offering compensation : in this approach the service provider secures land through acquisition or long term contracts. We describe the game rules and procedures for the implementation of ecological compensation, and we emphasize the need for consistency of these measures with land based policies. The property aspects, the concept of expectation and the consultation with the agricultural sector are for us the main determinants of the effectiveness of such measures.